Kunst in der Deutschen Bank Luxembourg S.A. - Baselitz, Georg; Baum, Peter; Brandler, Gunhild; Brandstetter, Alois; Britsch, Eckart; Burkhagen, M.M.; De Werd, Guido; Elsen, Thomas; Flügge, Matthias; Freitag, Michael; Gallwitz, Klaus; Gassner, Hubertus; et al. (Mainz : Verlag Hermann Schmidt, 1997)
Baselitz, Georg ; Böttcher, Joachim ; Damisch, Gunter ; Droese, Felix ; Eisel, Fritz ; Falke, Friedhelm ; Fetting, Rainer ; Förg, Gunther ; Fuhr, Ellen ; Handler, Rolf ; Hebenstreit, Manfred ; Ter Hell ; Höckelmann, Antonius ; Hödicke, Karl Horst ; Immendorff, Jörg ; Juretzek, Tina ; Keidel, Barbara ; Kiecol, Hubert ; Kirkeby, Per ; Knoebel, Imi ; Koberling, Bernd ; Krieg, Dieter ; Libuda, Walter ; Lüpertz, Markus ; McLean, Bruce ; Metzkes, Harald ; Middendorf, Helmut ; Mields-Kratochwil, Liz ; Moser, Maria ; Neumann, Max ; Penck, A.R. ; Recker, Anna ; Richter, Christiane ; Roda, Fernand ; Rückriem, Ulrich ; Schack, Philipp ; Scheibl, Hubert ; Scheuerecker, Hans ; Schumacher, Emil ; Stötzer, Werner ; Tadeusz, Norbert ; Tessmer, Heinrich ; Troschke, Wolfgang ; Voss, Jan ; Wercollier, Lucien ; Wukolow, Oleg
biog., geselect. tent. per kunstenaar [2 p.]
Duits
boek